INFLUENCE OF CD36 RS3211938 POLYMORPHISM ON HDL LEVELS IN BRAZILIAN SICKLE CELL ANEMIA PATIENTS - Rios, JO; Azouzi, S; Lobo, CC; Bonini-Domingos, CR [UNESP] (Elsevier, 2024)
Introduction Patients with sickle cell anemia (SCA) often exhibit reduced levels of high-density lipoprotein (HDL), which may be attributed to factors such as chronic inflammation, hemolysis, and oxidative stress. The CD36 gene, particularly the SNP rs3211938, regulates fatty acid metabolism and has been shown in other conditions, such as diabetes mellitus, to affect HDL levels. Alterations in lipid profiles and HDL functionality may potentially increase cardiovascular risk in individuals with SCA. Objective This study aimed to investigate whether CD36 gene polymorphisms influence HDL levels in SCA patients. Material and methods A Brazilian cohort of 190 patients with SCA was included, comprising 92 men and 98 women, with a mean age of 25.5 years (ranging from 15 to 56 years). All participants were confirmed as HbSS through high-performance liquid chromatography and molecular analysis. DNA was extracted from leukocytes obtained from total blood using the phenol/chloroform method. Genotyping of the CD36 gene was performed using the TaqMan assay. The association between genotypes and HDL levels was assessed using analysis of variance (ANOVA) to identify significant differences in HDL levels among different genotypes. Tukey's multiple comparison test was subsequently applied to determine which genotype pairs showed significant differences in HDL levels. All statistical analyses were conducted using RStudio, with the significance level set at p < 0.05. Results Genotyping revealed that 171 individuals carried the wild-type allele TT, 4 carried the mutant allele GG, and 15 carried the TG allele. Hardy-Weinberg equilibrium analysis showed allele frequencies of 0.93 for TT and 0.07 for GG, with a Chi2value of 17.7. ANOVA demonstrated a significant difference in HDL levels among the genotypes (F(2, 105) = 4.163, p = 0.0182). Tukey's test revealed that the mean difference in HDL levels between the TG and GG genotypes was 300.75, with a 95% confidence interval (CI) ranging from 20.42 to 581.08, indicating a significant difference (p = 0.0324). However, no significant differences were observed in HDL levels between the TT and GG genotypes (mean difference of 173.78; 95% CI: -79.50 to 427.05; p = 0.2371) or between the TT and TG genotypes (mean difference of -126.97; 95% CI: -257.36 to 3.41; p = 0.0580). Discussion The observed increase in HDL levels in individuals with the TG genotype may indicate a positive modulation of HDL functionality, which is particularly relevant for the SCA population given their predisposition to an adverse lipid profile and increased cardiovascular risk. The lack of significant differences in HDL levels between the TT and GG genotypes or the TT and TG genotypes suggests that the presence of the G allele, even in heterozygosity, may be sufficient to positively influence HDL levels. These findings align with previous studies implicating CD36 polymorphisms in altering lipid levels, particularly HDL, in other clinical conditions. Conclusion Our findings suggest that the rs3211938 polymorphism in the CD36 gene may play a significant role in determining HDL levels in SCA patients, particularly by increasing levels in individuals with the TG genotype. This discovery may have important implications for clinical management and the development of therapeutic strategies aimed at improving lipid profiles and reducing cardiovascular risk in this specific patient population.